فاعلية برنامج مقترح وفقا لنموذج التصميم العام لتدريس مقرر المدخل إلى تكنولوجيا التعليم على التحصيل الدراسي لطلاب المستوى الثاني بكلية التربية - جامعة الخرطوم (ADDIE) - حويري، عليش عبدالرحيم البشير; الحسن، عصام إدريس كمتور (جامعة الخرطوم - كلية التربية, 2019)
يهدف هذا البحث إلى التعرف على فاعلية برنامج إلكتروني مقترح وفقا لنموذج التصميم العام (ADDIE) لتدريس مقرر المدخل إلى تكنولوجيا التعليم على التحصيل الدراسي لطلاب المستوى الثاني بكلية التربية جامعة الخرطوم. استخدم الباحثان المنهج شبه التجريبي، وتكون مجتمع البحث من طلاب المستوى الثاني بكلية التربية جامعة الخرطوم، حيث تم اختيار عينة بطريقة عشوائية قوامها 152 طالبا وطالبة من طلاب المستوى الثاني تمثل 38% من المجتمع الأصلي تم تقسيمهم إلى مجموعتين متكافئتين: مجموعة تجريبية قوامها 76 طالبا وطالبة وأخرى ضابطة قوامها 76 طالبا وطالبة. استخدم الباحثان الاختبار التحصيلي كأداة لجمع البيانات، وباتباع الأساليب الإحصائية الملائمة تم تحليل البيانات باستخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية SPSS. خلص البحث إلى مجموعة من النتائج أهمها: تصميم وبناء برنامج إلكتروني مقترح وفقا لنموذج ADDIE لتدريس مقرر المدخل إلى تكنولوجيا التعليم، وجود فروق ذات دلالة إحصائية عند مستوى الدلالة 0.05 بين متوسطات درجات طلاب المجموعة التجريبية الذين درسوا المقرر إلكترونيا باستخدام البرنامج الإلكتروني المقترح وفقا لنموذج ADDIE ومتوسطات درجات طلاب المجموعة الضابطة الذين درسوا المقرر نفسه وفقا للطريقة التقليدية في الاختبار التحصيلي البعدي ولصالح المجموعة التجريبية. توجد فروق ذات دلالة إحصائية عند مستوى الدلالة 0.05 بين متوسطات تحصيل درجات طلاب المجموعة التجريبية التي درست المقرر إلكترونيا باستخدام البرنامج الإلكتروني المقترح وفقا لنموذج ADDIE تعزى لمتغير التخصص (علمي، أدبي) لصالح التخصص العلمي. وبناء على تلك النتائج أوصى الباحثان بالأخذ بفكرة البرنامج الإلكتروني المصمم وفقا لنموذج ADDIE وتطبيقه في تدريس مقررات تكنولوجيا التعليم، والعمل على التوظيف الأمثل للبرامج الإلكترونية التعليمية التفاعلية في عملية التدريس في مراحل التعليم الجامعي، وزيادة عدد ساعات التدريس النظرية في مقرر المدخل إلى تكنولوجيا التعليم لطلاب المستوى الثاني بكلية التربية جامعة الخرطوم.
This research aims at identifying the effectiveness of an electronic programm according to the ADDIE model to teach the syllabus, of an introduction to Instructional technology and measure its impact on academic achievement of students of the second level at the Faculty of Education, University of Khartoum. The researchers adopted the quasi -experimental method. The research population consisted of all the students of the second year at the Faculty of Education University of Khartoum. A random sample of 152 male and female students from the second year representing 38% of the target population was selected. They were divided into two equal groups; the experimental and the control group, each included 76 male and female students. The researchers used the test as tool for data collection. Using the appropriate methods of analysis, the data was analyzed by using the Statistical Package for Social Sciences (SPSS). The research reached a number of findings, the most important of which: a designed and built up an electronic programm based on to the ADDIE model to teach the syllabus of introduction instructional technology. The findings of the quasi – experimental methodology showed that there are statistically significant differences at the significance point 0.05 between means of scores of the experimental group who were taught the syllabus electronically, using the suggested electronic programm, based on to the ADDIE model, and means of scores of the control group who were taught the syllabus in the traditional method, in the post- test in favor of the experimental group. There are statistically significant differences at the significance level 0.05 between means of scores of the experimental group who were taught the syllabus electronically, using the suggested electronic programm, based on the ADDIE model due to major (Science/Art) variable in favor of the science major. Based on the previous findings, the researchers recommended the following: Adopting the idea of a designed electronic programm and applying it in Teaching Instructional Technology syllabuses, Also working on the optimal use of the interactive electronic education programmes in teaching at different level of university education. They also recommends increasing the number of the theoretical hours in teaching the syllabus of an introduction to instructional technology for the students of the second year at the Faculty of Education, University of Khartoum
Keywords: طلبة الجامعة -- جامعة الخرطوم -- التعليم الإلكتروني -- التحصيل الدراسي